Factors Affecting the First Service Conception Rate of Cows in Smallholder Dairy Farms in Bangladesh. Issue 3 (30th October 2012) - Siddiqui, MAR; Das, ZC; Bhattacharjee, J; Rahman, MM; Islam, MM; Haque, MA; Parrish, JJ; Shamsuddin, M
Contents The successful outcome of an insemination is a combination of both male and female fertility‐linked factors. We investigated the first service conception rate of cows at artificial insemination (AI) in the smallholder dairy farms in Bangladesh. Frozen straws were prepared from ejaculates of Bos indicus (n = 7) and Bos indicus × Bos taurus (n = 7) AI bulls. Fertility was determined from 6101 first services in cows that were performed by 18 technicians in four regions between April 2004 and March 2005. Pregnancy was diagnosed by rectal palpation between 60 and 90 days post‐insemination. The Asian version of Artificial Insemination Database Application (AIDA ASIA) was used for bulls‐, cows‐ and AI‐related data recording, and later retrieved for analysis. The mean ± SD number of inseminations performed from individual bulls and their conception rates were 436.0 ± 21.6 and 50.7 ± 1.9%, respectively. Logistic regression demonstrated body condition scores (BCS), heat detection signs, months of AI and their interactions had greatest effects (odds ratios: 1.24–16.65, p < 0.04–0.001) on first service conception rate in cows. Fertility differed (p < 0.02–0.001) between the regions, previous calving months, months of AI, BCS, parity and heat detection signs of cows. Inseminations based on mounting activity (n = 2352), genital discharge (n = 3263) and restlessness and/or other signs (n = 486) yielded a conception rate of 53.6%, 48.8% and 50.1%, respectively (p < 0.05). Conception rate between technicians ranged between 43.4% and 58.6% (p < 0.05). The days interval from calving to first service (overall mean ± SD = 153.4 ± 80.6) had relationship (p < 0.001) with BCS, months of previous calving and parity of the cows. Fertility at AI in smallholder farms can be improved by training farmers on nutrition and reproductive management of the cows.